Selegiline a molecule with innovative potential - Tábi Tamás; Vécsei László; Youdim Moussa B.; Riederer Peter; Szökő Éva (2020)
Monoamine oxidase B (MAO-B) inhibitors have an established role in the treatment of Parkinson's disease as monotherapy or adjuvant to levodopa. Two major recognitions were required for their introduction into this therapeutic field. The first was the elucidation of the novel pharmacological properties of selegiline as a selective MAO-B inhibitor by Knoll and Magyar and the original idea of Riederer and Youdim, supported by Birkmayer, to explore its effect in parkinsonian patients with on-off phases. In the 1960s, MAO inhibitors were mainly studied as potential antidepressants, but Birkmayer found that combined use of levodopa and various MAO inhibitors improved akinesia in Parkinson's disease. However, the serious side effects of the first non-selective MAO inhibitors prevented their further use. Later studies demonstrated that MAO-B, mainly located in glial cells, is important for dopamine metabolism in the brain. Recently, cell and molecular studies revealed interesting properties of selegiline opening new possibilities for neuroprotective mechanisms and a disease-modifying effect of MAO-B inhibitors.